1997
DOI: 10.1111/j.1751-1097.1997.tb03155.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Noninvasive in vivo Measurements of Photosensitizer Uptake Based on a Diffusion Model of Reflectance Spectroscopy

Abstract: This study compares the photosensitizer concentration measured noninvasively in vivo by diffuse reflectance spectroscopy with the results of postmortem tissue solubilization and fluorometric assay. The reflectance spectrometer consists of a fiber optic surface probe, spectrometer and charge-coupled device (CCD) array detector. The surface probe has eight detection fibers separated from the light source fiber by distances ranging from 0.85 to 10 mm. The imaging spectrometer disperses the light from each detecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 24 publications
5
47
0
Order By: Relevance
“…The uptake and retention of i.v. administered photosensitizer by tumor tissue is one of several fundamental determinants of the clinical effectiveness of PDT as mentioned by Weersink, R. A., et al, 1997, Chen, Q., et al., 1996, Love, W. G., et al, 1996 and Windahl, T., et al, 1993 which comply with our obtained results that study of PS tissue uptake reflects many aspects that facilitate the understanding and how we can optimally benefit from this useful treatment modality [17][18][19][20]. Using Matlab to study and analyze tissue auto fluorescence was applied by Kamath SD and Mahato KK 2007 the demonstrated that Matlab is a good tool for the spectral analysis and classification for discrimination of autofluorescence spectra of pathologically certified normal, premalignant, and malignant oral tissues [21].…”
Section: Discussionsupporting
confidence: 81%
“…The uptake and retention of i.v. administered photosensitizer by tumor tissue is one of several fundamental determinants of the clinical effectiveness of PDT as mentioned by Weersink, R. A., et al, 1997, Chen, Q., et al., 1996, Love, W. G., et al, 1996 and Windahl, T., et al, 1993 which comply with our obtained results that study of PS tissue uptake reflects many aspects that facilitate the understanding and how we can optimally benefit from this useful treatment modality [17][18][19][20]. Using Matlab to study and analyze tissue auto fluorescence was applied by Kamath SD and Mahato KK 2007 the demonstrated that Matlab is a good tool for the spectral analysis and classification for discrimination of autofluorescence spectra of pathologically certified normal, premalignant, and malignant oral tissues [21].…”
Section: Discussionsupporting
confidence: 81%
“…22 Similar results have also been reported by Cubeddu et al 21 for AlS 2 Pc, where the in vivo absorption spectrum peaked at 685 nm compared with 672 nm for absorption in aqueous solution 23 and cell cultures. 24 Furthermore, Weersink et al 19 found a redshift to ϳ680 nm of the absorption peak of tetrasulphonated aluminum phthalocyanine ͑AlS 4 Pc͒ in rabbit skin, which is in agreement with the findings for AlS 2 Pc. Stratonnikov et al, 18 however, found a redshift of the absorption peak of Photosence (NIOPIC, Russia) in human lip in vivo of only 4 nm, as compared with the aqueous solution.…”
Section: Discussionsupporting
confidence: 80%
“…Because melanin and water have a wavelength-dependent absorption coefficient, the distribution of these components (melanin, water) influences the optical properties of skin [34]. The light absorption by water in tissue is higher at λ =1064 nm than at visible wavelengths [35]. Thereby, the high diffuse reflectance, which was also found at λ=1064 nm with short radius, may arise from high absorption by water in the skin tissue.…”
Section: Resultsmentioning
confidence: 91%